Circulating CD34+ cells and active arterial wall thickening among elderly men: A prospective study - Shimizu, Yuji (Sci Rep, 2020)
Age-related physical changes, such as low-grade inflammation and increased oxidative stress, induce endothelial repair and cause active arterial wall thickening by stimulating the production of CD34+ cells (the principal mediators of atherosclerosis). Despite this, aggressive endothelial repair (progressing atherosclerosis) might cause a wasting reduction in CD34+ cells, which could result in a lower capacity of endothelial repair and hypertension. As yet, no prospective study has clarified the association of circulating CD34+ cells with active arterial wall thickening. We conducted a prospective study of 363 men aged 60–69 years who participated in a general health check-up at least twice from 2014–2017. The circulating CD34+ cell count was significantly positively associated with active arterial wall thickening among subjects without hypertension (n = 236), but not among subjects with hypertension (n = 127). The fully adjusted odds ratios (ORs) of active arterial wall thickening for the logarithmic circulating CD34+ cell count were 1.83 (1.19, 2.84) and 0.69 (0.36, 1.32) for subjects without and with hypertension, respectively. Circulating CD34+ cells are positively associated with active arterial wall thickening in subjects without hypertension. This study demonstrates a means to clarify the mechanisms of endothelial repair in elderly subjects.